A review of the genus Aulolaimus de Man, 1880 (Axonolaimidae: Aulolaiminae n. subfam.) with notes on the synonymy of the genus Pandurinema Timm - Jairajpuri, M. S.; Hooper, D. J. (Journal of Helminthology, 1968)
Locality: ; Cabinet:
NeMys doc_id: 4941